Exploring Java 9 Build Modularized Applications in Java - Cheng, Fu (Apress, 2018)
Discover all the new features and changes in Java 9, including module systems-JPMS or Project Jigsaw. This book covers the whole Java application development life cycle. You'll review all the important concepts, including module descriptor, unnamed module, automatic module, and command line tools. Exploring Java 9 also serves as a practical guide for migration to module systems. Code samples from real-world scenarios solidify a foundation for learning and development and allow you to apply best practices in actual development. Additionally, you'll learn about concurrency, ECMAScript 6 features in Nashorn and Parser API, stack-walking API, Stream and Optional, utilities classes, and I/O. And it's now possible to build modularized applications in Java. You'll see how JPMS affects not only the JDK itself, but also applications that are developed upon it.